Treating patients with cancer amidst the COVID-19 pandemic: experience of a regional hospital in the Piedmont region in northern Italy. Issue 5 (October 2020) - Garrone, Ornella; Denaro, Nerina; Ruatta, Fiorella; Vanella, Paola; Granetto, Cristina; Vandone, Anna Maria; Occelli, Marcella; Cauchi, Carolina; Ricci, Vincenzo; Fea, Elena; Di Costanzo, Gianna; Colantonio, Ida; et al.
Background: The coronavirus disease 2019 (COVID-19) pandemic is posing an unprecedented dilemma to oncologists worldwide, forcing them to decide whether to continue or suspend treatments in order to protect their most vulnerable patients from infection. After the first report from China, the outbreak spread rapidly worldwide. To, date no clear indications on how to treat patients with cancer with COVID-19 infection are available. Methods: We report data on 21 patients with cancer referred to a single medical oncology unit of a general hospital from mid-March to April 23, 2020. Results: Nine patients were on active cancer therapy during the infection and all stopped medical treatments. Overall 8 patients developed pneumonia and 6 patients died of COVID-19. Conclusion: The management of patients with cancer during the pandemic should be carefully balanced and discussed among oncologists and other key professionals involved in the treatment of this vulnerable group of patients, in order to balance the risk of treatment and the risk of infection.